HarvestPlus-led Delivery Efforts Resulted in an Estimated 48.5 Million People Consuming Biofortified Crops in 2020 - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
HarvestPlus leads the development and delivery of biofortified crops, and the research on their efficacy, effectiveness, acceptability and adoption. By the end of 2020, 393 biofortified varieties of 12 staple crops were approved for planting in 41 countries, and an estimated 9.7 million farming households (48.5 million people) were growing and consuming biofortified crops across 19 countries Africa, Asia, and Latin America. Consumption of biofortified crops are proven to improve not only nutrition and health, but also other livelihood outcomes.